Standar Operasional Prosedur Kantor Imigrasi Dalam Penanganan Wisatawan Asing Yang Menyalahgunakan Izin Tinggal Kunjungan Di Bali - Susilo, Muhammad Itsar; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i01.p25, 2019)
This research was conducted to seek the Standard Operating Procedures of the Immigration Office in Handling Foreign Tourists Who Misused Permits for Visiting Visa in Bali. The research used in study is qualitative descriptive. The informant determination technique used was the Purposive Procedure technique. The data sources used were primary and secondary data sources. Primary data in this study were data that come from direct observation to the location of the study by observation and interview. While secondary data in this study were data obtained from documentation or literature studies to supplement primary data. The results showed that the supervision and deportation of foreign nationals at the Ngurah Rai Special Class I Immigration Office was carried out to the maximum by immigration officers, starting from the coming till being out of Indonesia, the process was in accordance with Law Number 6 of 2011 and Regulations The Government of the Republic of Indonesia Number 31 of 1994 concerning Procedures for Supervision of Foreigners and Immigration Measures as well as provisions that apply to the stages of foreigners is carried out by the process of detention in the detention room of the Immigration Office, given the action by the Head of the Immigration Office. Keywords: Immigration Office, Foreign Tourists, Visa Permits